Insider's Guide to Community College Administration - Jensen, Robert; Giles, Ray; Kirklin, Pat; American Association of Community Colleges ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2000)
This book offers advice on the skills and attitudes needed to succeed as a community college leader. As one begins to move up the organizational ladder from program director or assistant dean to dean or vice president, the sphere of influence expands dramatically. There is a greater need to be able to see how programs and decisions affect the institution, both horizontally and vertically. Horizontally involves the wide spectrum of programs offered by the college; vertically refers to the administrative chain of command as well as budgets, personnel, politics, and policies. The book's chapters cover topics such as: (1) the difference between being president and being CEO; (2) hiring and managing a consultant; (3) institutional politics; (4) building a faculty leadership; (5) selecting the board chair; and (6) making the best of a mismatch. Finally, the ten truths of community college leadership are presented, some of which are: (1) every decision made has three elements--educational, fiscal, and political; (2) organizational conspirators are alive and well; (3) leadership and management are different skills; and (4) not all rocks are meant to be turned over. (JA)
Availability: Community College Press, P.O. Box 311, Annapolis Junction, MD 20701 ($24). Tel: 800-250-6557 (Toll Free; Web site: http://www.aacc.nche.edu.
Administrators.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Deans; College Administration; College Presidents; Community Colleges; Governance; Leaders Guides; Leadership; Leadership Qualities; School Administration; Two Year Colleges; Books; Guides, Non-Classroom.